Factors influencing continuance of usage intention towards a gamified e-quiz mobile application among Malaysian higher learning students - Roslan, Rosfuzah (2023)
It is expected that gamification in education will be the luring factor and be able to sustain the interest of the current generation. Previous studies have identified various factors that influenced individuals’ decisions when accepting mobile technology. However, studies related to factors influencing post-acceptance of a gamified mobile technology are scarce. Therefore, this study aims to produce a fitting structural model consisting of factors influencing the continuance usage intention among the Malaysian higher learning students towards a gamified e-quiz mobile application. The research integrated the Expectation Confirmation Model (ECM) with the Extended Unified Theory of Acceptance and Use of Technology (UTAUT2), along with two additional constructs, trust and consumer engagement that were derived from Mcknight et al.’s (2011) Trust in Technology Theory and Service-Dominant (S-D) Logic Theory, respectively. Following that, 10 variables were investigated in which eight are the exogenous variables namely, (i) confirmation of expectation, (ii) perceived enjoyment, (iii) perceived ease of use, (iv) social influence, (v) facilitating condition, (vi) consumer engagement and (vii) trust. On the other hand, the other three variables are the endogenous variables that comprises (i) satisfaction, (ii) perceived usefulness and (iii) continuance usage intention. Construct satisfaction, as a mediator towards continuance usage intention, between (i) trust, (ii) perceived usefulness and (iii) perceived enjoyment, was also investigated. The study implemented the correlational research design conducted on the Malaysian higher learning students. With the total population of 560 first-year students who are the existing users of the technological product, 269 sample sizes managed to be retained for further analysis. Based on the analysis conducted, the ‘in-sample’ predictive power (i.e., explanatory power) of the model indicates substantial predictive accuracy. More importantly, the model exhibits higher value (i.e., predictive power) by proving that it could predict future dataset (i.e., ‘out-of-sample’). In conclusion, the significant integration was proven by some of UTAUT2 explanatory variables (i.e., perceived enjoyment, perceived ease of use and perceived usefulness), as well as construct trust derived from the Trust in Technology Theory, with the ECM ii constructs (i.e., satisfaction, confirmation, perceived usefulness). In the end, the study managed to provide a theoretical basis in explaining the continuance use intention towards a gamified e-quiz mobile application. Additionally, these findings emphasise the importance of improving the gamification aspects of the technological product based on the factors studied, in order to secure the longevity of an educational application, produced by the higher learning institute.